Exercise engagement drives changes in cognition and cardiorespiratory fitness after 8 weeks of aerobic training in sedentary aging adults at risk of cognitive decline - Hinchman, Carrie A.; Cabral, Danylo F.; Ciesla, Marissa; Flothmann, Marti; Nunez, Christina; Rice, Jordyn; Loewenstein, David A.; Kitaigorodsky, Marcela; Cahalin, Lawrence P.; Rundek, Tatjana; Pascual-Leone, Alvaro; Cattaneo, Gabriele; et al. (Frontiers in Rehabilitation Sciences, 2022)
Background: With our aging population, many individuals are at risk of developing age-related cognitive decline. Physical exercise has been demonstrated to enhance cognitive performance in aging adults. This study examined the effects of eight weeks of aerobic exercise on cognitive performance and cardiorespiratory fitness in sedentary aging adults at risk for cognitive decline. Methods: Fifty-two participants (age 62.9±6.8, 76.9% female) engaged in eight-weeks moderate-to high-intensity exercise (19 in-person, 33 remotely). Global cognition was measured by the Repeatable Battery for the Assessment of Neuropsychological Status, the Delis-Kaplan Executive Function System, and the Digit Span subtest of the Wechsler Adult Intelligence Scale (WAIS) Fourth Edition. Cardiorespiratory fitness was measured via heart rate recovery at minute 1 (HRR1) and 2 (HRR2), and exercise engagement (defined as percent of total exercise time spent in the prescribed heart rate zone). We measured pre and post changes using paired t-tests and mixed effects models, and investigated the association between cardiorespiratory and cognitive performance using multiple regression models. Cohen’s d were calculated to estimate effect sizes. Results: Overall, 63.4 % of participants demonstrated high engagement (≥ 70% total exercise time spent in the prescribed heart rate zone). There were significant pre-post improvements in verbal fluency and verbal memory, and a significant decrement in working memory, but these were associated with small effect sizes (Cohen’s d <0.5). Concerning cardiorespiratory fitness, there was a pre-to-post significant improvement in HRR1 (p = 0.01, d = 0.30) and HRR2 (p < 0.001, d = 0.50). Multiple regressions revealed significant associations between cardiorespiratory and cognitive performance, but all were associated with small effect sizes (Cohen’s d <0.5). Interestingly, there were significant between-group differences in exercise engagement (all p < 0.001), with remote participants demonstrating greater exercise engagement than in-person participants. Conclusion: Improvements in cognition and cardiorespiratory fitness were observed after eight weeks of moderate to high-intensity exercise in aging adults. These results suggest that committing to a regular exercise regimen, even for a brief two-month period, can promote improvements in both cardiorespiratory fitness and cognitive performance, and that improvements are driven by exercise engagement.